Pendidikan Karakter Dalam Cerita Panca Tantra - Pratama Yasa, I Putu Wahyu (Jayapangus Press, 2021)
Panca Tantra is a popular story favored by the Hindu community in Bali called Tantri. Panca Tantra has a religious dimension, namely carrying out purification and self-emptying based on the saturation of routines that allow recreation of the inner world. The Five Tantras in the Vedic codification are included in the Nibandha class. The problems to be discussed in this study include; 1) What is the structure of the text in the Panca Tantra story?, 2) What Hindu religious teachings are contained in the Panca Tantra story? 3) How is character education in Five Tantra? In general, this research aims to preserve the nation's cultural heritage, especially Balinese culture. It is hoped that this research, in the Stories of Panca Tantra, will be understood and internalized to be carried out in everyday life both among academics and the general public. The theory used is structuralism theory and character theory. The research method uses (1) Interview, (2) Observation, (3) Literature Study, and (4) Documents. Data analysis methods and techniques use (1) data reduction (2) data presentation (3) inference or verification. In the method and presentation of results using formal and informal methods. The results of the study show that the general description of the research object includes a synopsis of the text of the five tantra stories, the prose of the text of the five tantra stories, the structure of the text of the five tantra stories, and contains teachings 1) the teachings of sraddha bhakti 2) the teachings of Tri Hita Karana 3) the teachings of Tri Kaya Parisudha; 4) Subha Karma teachings; 5) Asubha Karma) and character education contained in the five tantra stories which include; a) religious character education; b) honesty character education; c) disciplinary character education; d) character education with leadership spirit e) social care character education and character education of the Panca Tantra.